Recent Advances and Challenges toward Efficient Perovskite/Organic Integrated Solar Cells - Soonil Hong; Jinho Lee (Energies, 2022)
Recently, emerging third-generation photovoltaic technologies have shown rapid progress in device performance; the power conversion efficiencies (PCEs) of organic bulk heterojunction (BHJ) and perovskite solar cells (PSCs) are now surpassing 19% and 25%, respectively. Despite this dramatic enhancement, their efficiencies are theoretically limited based on the detailed balance model which accounts for inevitable loss mechanisms under operational conditions. Integrated solar cells, formed by monolithically integrating two photoactive layers of perovskite and BHJ with complementary absorption, provide a promising platform for further improvement in solar cell efficiency. In perovskite/BHJ integrated solar cells (POISCs), high bandgap perovskite offers high open-circuit voltage with minimal losses while low bandgap organic BHJ extends absorption bandwidth by covering the near-infrared region, resulting in additional photocurrent gain. Different from conventional tandem solar cells, integrated solar cells contain merged photoactive layers without the need for complicated recombination layers, which greatly simplifies fabrication processes. In this review, we summarize the recent progress in POISCs, including operational mechanism and structural development, and remaining challenges on the road toward efficient devices.